LEKSIKON SAMIN SEBAGAI CERMIN PANDANGAN DUNIA PENUTURNYA - Suhandan, Suhandan (LITERA, 2015)
Abstract The Samin people are a group of Javanese speakers. However, the Javanese they use is a little different from the common Javanese in some ways. For example, they use some distinctive lexicons such as rukunan "˜husband/wife’, pondhokan "˜house’, turun "˜child’, and so on. This article discusses the distinctive lexicons in the Samin community to explain why they use such unique lexicons. The discussion employs the framework of anthropological linguistics studying linguistic facts in a broad sociocultural context. The findings reveal that the use of distinctive lexicons by the Samin community is not coincidental, but related to their perspectives on viewing things labeled by the lexicons; how they do so is influenced by the Saminism ideology. In addition, it is also revealed that in some instances, for the Samin community, the lexicons are not just labels that mark something, but also tools to interpret something.